"A Terrible Beauty": Iris Murdoch's Irish Novel, The Red and the Green. Issue 8 (17th November 2019) - Dooley, Gillian; White, Frances
ABSTRACT: Iris Murdoch was born in Ireland in 1919, and although she grew up in England and lived there all her life she always identified herself as "Anglo-Irish". The Red and the Green (1965), set in Dublin in the week leading up to the Easter Rising in 1916, is Murdoch's only historical novel. This work is in many ways concerned with the same kinds of personal drama that animate her other fiction, weaving historical events into the fabric of a complicated narrative involving several members of an extended Anglo-Irish family. Although the characters are fictional, there are many small and unobtrusive hints of her own personal identification with the material scattered throughout the text. We discuss these echoes in the work, and also consider what led her to depart in this single case from her usual practice of writing novels set in a more or less contemporary time and concerned only with fictional events. We propose that Yeats' poem "Easter 1916" is an important element in the structure of Murdoch's novel, and consider the consequences of the pervasive influence of Yeats on this novel in the light of Murdoch's still contested status as an Irish novelist.